The Influence of Daughter's Attachment to Father on Social Emotional Development - Santyani, Wina; Suryanti, Dewi Sri (KINDERGARTEN: Journal of Islamic Early Childhood Education, 2024)
This study aims to determine the effect of a daughter's attachment to her father on the socio-emotional development of children aged 4-6 years in Babussalam Kindergarten, Pekanbaru. This study uses a quantitative approach with a correlational method. The subjects of this study were fathers and daughters aged 4-6 years in Babussalam Kindergarten with the object of research namely the influence of the attachment of daughters with fathers on the socio-emotional development of children aged 4-6 years. Data collection techniques used are questionnaires and documentation. The data analysis technique uses product moment correlation with the help of the SPSS windows version 22.0 program. The research hypothesis is that there is an influence of the daughter's attachment to the father on social emotional development. The results of data analysis obtained tcount = 7,378 with a significant level = 0.001 and ttable = 2,228. The results of these calculations show tcount > ttable (7,378 > 2,228). So it can be concluded that there is an influence of the attachment of daughters with fathers on the social emotional development of children aged 4-6 years in Babussalam Kindergarten Pekanbaru.Keywords : Attachment, Social Emotional DevelopmentABSTRAK. Penelitian ini bertujuan untuk mengetahui pengaruh kelekatan anak perempuan dengan ayah terhadap perkembangan sosial emosional anak usia 4-6 tahun di TK babussalam pekanbaru. Penelitian ini menggunakan pendekatan kuantitatif dengan metode korelasional. Subjek penelitian ini adalah ayah dan anak perempuan yang berusia 4-6 tahun di TK Babussalam dengan objek penelitian yaitu pengaruh kelekatan anak perempuan dengan ayah terhadap perkembangan sosial emosional anak usia 4-6 tahun. Teknik pengumpulan data yang digunakan yaitu angket atau kuisioner dan dokumentasi. Teknik analisis data menggunakan korelasi product moment dengan bantuan program SPSS windows versi 22.0. Hipotesis penelitian adalah terdapat pengaruh kelekatan anak perempuan dengan ayah terhadap perkembangan sosial emosional. Hasil analisis data diperoleh thitung = 7,378 dengan taraf signifikan = 0.001 dan ttabel = 2,228. Hasil dari perhitungan tersebut menunjukkan thitung > ttabel (7,378 > 2,228). Maka dapat disimpulkan bahwa terdapat pengaruh kelekatan anak perempuan dengan ayah terhadap perkembangan sosial emosional anak usia 4-6 tahun di TK Babussalam Pekanbaru. Kata Kunci : Kelekatan, Perkembangan Sosial Emosional